Pengaruh Metode Discovery Learning terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas IV di Sekolah Dasar Negeri Nomor 104291 Sei Buluh Kabupaten Serdang Bedagai Kecamatan Teluk Mengkudu - Intan Nurzannah; Thessa Herdyana; Nizmi Putri (Medan Resource Center, 2025)
This study investigates the effect of the discovery learning method on fourth-grade students’ interest in Civic Education at State Elementary School Number 104291 Sei Buluh, Serdang Bedagai Regency, Teluk Mengkudu District. Classroom observations indicated low engagement and limited conceptual understanding under conventional, teacher-centred instruction. The research problem asks whether discovery learning significantly increases students’ interest in learning Civics. A quantitative pre-experimental design with a one-group pre-test–post-test was employed involving 17 fourth-grade students. Data were collected through questionnaires, observation, and documentation, with instruments validated through expert judgment and product-moment construct validity, and their reliability estimated using the Alpha coefficient. Data analysis used the Liliefors test and t-test supported by SPSS. The results show a statistically significant increase in students’ learning interest after the implementation of discovery learning (sig. 2-tailed = 0.000 < 0.05), indicating rejection of the null hypothesis and acceptance of the alternative hypothesis. The study concludes that discovery learning positively influences students’ interest in Civic Education and recommends its broader use to foster active participation and deeper engagement in elementary Civics classrooms.